The characteristics of methicillin-resistant Staphylococcus aureus co-infection in COVID-19 pneumonia - Feifei Gu; Yuyi Zhang; Jingyong Sun; Wei Guo; Lizhong Han (Frontiers in Cellular and Infection Microbiology)
Methicillin-resistant Staphylococcus aureus (MRSA) stands as a pervasive and important pathogen in the co-infections during the COVID-19 pandemic given its high morbidity and mortality. This study aimed to characterize MRSA isolates obtained from COVID-19 pneumonia with MRSA co-infection patients during the COVID-19 pandemic wave in China from 2022 to 2024. Fifty MRSA isolates collected form COVID-19 pneumonia with MRSA co-infection patients (MRSA-COC) and 50 MRSA isolates collected from MRSA pneumonia patients without COVID-19 (MRSA-CON) were enrolled in this study. Whole-genome sequencing, genomic epidemiology and comparative analysis were conducted to explore differences of MRSA isolates between two groups. Patients with MRSA-COC were significantly older (P=0.0492), had higher rates of severe pneumonia progression (P=0.0006), and carried greater comorbidity burdens. The time from hospital admission to MRSA detected was significantly shorter in MRSA-COC patients than in MRSA-CON patients (P=0.0141). Furthermore, MRSA-COC patients demonstrated significantly higher mortality rates compared with MRSA-CON patients (44% vs. 18%, P=0.0049). However, genomic analysis revealed no statistically significant differences in antimicrobial resistance gene or virulence factor genes between the MRSA-COC and MRSA-CON isolates. CC5 emerged as the predominant clone in both groups, with significantly higher prevalence in MRSA-COC isolates (88% vs. 66%, P=0.0090). The tst-positive ST5-MRSA-II strain was associated with concerning mortality rates in both MRSA-COC (50%) and MRSA-CON (20%) patients, underscoring the critical need for enhanced surveillance in MRSA pneumonia.